"Is it my job?" An exploratory qualitative analysis of medical specialists' adaptation strategies when addressing the health needs of people with intellectual disabilities. (June 2023) - Rinaldi, Romina; Batselé, Elise
Access to equal healthcare is a priority for people with intellectual disabilities. Most studies have focused on primary care providers; however, the administration of inclusive healthcare also relies on medical specialists, who should be considered a specific group because their practice varies significantly in this regard. Semi-directive interviews were conducted with 12 medical specialists to explore their representations regarding the care of people with intellectual disabilities. An inductive thematic analysis was applied to the data. The results highlighted a significant heterogeneity between practitioners' representations of people with intellectual disabilities in healthcare, current practices, and their perceptions and expectations in the process of ensuring quality care. This study highlights the importance of considering medical specialists' awareness raising and training to handle consultations with people with intellectual disabilities. From a broader perspective, a clear political framework to guide healthcare practices at the national level should be developed.